2020
DOI: 10.3389/fcimb.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Proteome Analysis Reveals RH36 Regulates Reproduction via Vitellin Uptake Mediated by HSP70 Protein in Hard Ticks

Abstract: Ticks are blood-sucking vector arthropods, which play an important role in transmitting pathogens between humans and animals. RH36 is an immunomodulatory protein expressed in the salivary glands, but not other organs, of partially fed Rhipicephalus haemaphysaloides ticks, and it reaches its peak on the day of tick engorgement. RH36 gene silencing inhibited tick blood feeding and induced a significant decrease in tick oviposition, indicating that another function of immunosuppressor RH36 was regulating tick rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous studies showed that the expression of HSC70 mRNA in ticks reached its highest level at the beginning of blood-feeding and remained at this high level until the semi-engorged status had been reached; in addition, the expression of HSC70 mRNA was significantly upregulated compared to that of unfed ticks [ 17 , 36 ]. In one study on ticks, following silencing of HSP70 using the interference RNA method, the attachment and average engorgement rates of these ticks on the host decreased significantly and the ticks suffered a mortality rate as high as 97.44% [ 37 ]. These findings suggest that HSC70 plays an important anticoagulation role during tick blood-sucking and blood-meal digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the expression of HSC70 mRNA in ticks reached its highest level at the beginning of blood-feeding and remained at this high level until the semi-engorged status had been reached; in addition, the expression of HSC70 mRNA was significantly upregulated compared to that of unfed ticks [ 17 , 36 ]. In one study on ticks, following silencing of HSP70 using the interference RNA method, the attachment and average engorgement rates of these ticks on the host decreased significantly and the ticks suffered a mortality rate as high as 97.44% [ 37 ]. These findings suggest that HSC70 plays an important anticoagulation role during tick blood-sucking and blood-meal digestion.…”
Section: Discussionmentioning
confidence: 99%
“… 2012 (Kapoor et al., 2012 ) Haemaphysalis spp., Rhipicephalus spp. (Wang, Wang, et al., 2020 ; Wang, Zhao, et al., 2020 ) Australia, Brazil, China, Columbia, Croatia, Germany, Iran, Italy, Norway, Thailand, Turkey, UK, USA, Viet Nam (Urbani et al., 2021 ) Avian‐like circovirus Tick associated circovirus 1 Circovirus Circoviridae ssDNA (+/−) NC_030199 Complete genome ? 2018 (Tokarz et al., 2018 ) I. scapularis (Tokarz et al., 2018 ) USA (Tokarz et al., 2018 ) Nayun tick torquevirus Unclassified Thetatorquevirus Anelloviridae ssDNA (+/−) KP141758 Partial genome ?…”
Section: Table A1mentioning
confidence: 99%
“… GIJA01018702.1 Rhipicephalus haemaphysaloides Orthomyxoviridae ssRNA(−) 2357 Zambezi tick virus 1 (MH267793.1) 77 One putative ORF; predicted protein contains homologues of Influenza RdRp subunit PB1 (PF00602) motif Wang, Wang, et al. ( 2020 ), https://doi.org/10.3389/fcimb.2020.00093 GGIX01201876.1 Ixodes scapularis Chuviridae ssRNA(−) 728 Bole tick virus 3 (MH688550.1) 87 One putative ORF; predicted protein contains homologues of Mononegavirales RdRp (PF00946) motif H. M. Robertson, Unpublished. …”
Section: Table A1mentioning
confidence: 99%